Manajemen Sumber Daya Insani Berbasis Syariah: Implementasi Nilai-Nilai Islam dalam Pengelolaan Karyawan di LKP English Academy Bengkulu - Ade Riska Nur Astari (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
This research aims to explore the implementation of Islamic values in human resource management at LKP English Academy Bengkulu and its impact on employee performance and welfare. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation analysis. The informants in this study consisted of 11 employees. The results showed that the application of Islamic values in the recruitment and selection process, training and development, performance appraisal, and compensation and reward system has a significant positive impact on employee performance and welfare. Transparent and fair recruitment process transparent and fair recruitment process, training that includes technical and spiritual aspects, objective performance appraisal, and a compensation system based on the principles of justice and welfare have succeeded in increasing employee motivation, competence, and job satisfaction. The distribution of informants' positions shows that the majority are teaching tutors (86%) with directors, academic managers, administrative staff, and facilities and infrastructure staff each at (100%). The implementation of Islamic values in LKP English Academy Bengkulu creates a fair, transparent and humane work environment, which ultimately improves the overall performance of the organization.